Attitudes of Couples towards Family Planning Methods in Orhionmwon Local Government Area of Edo State, Nigeria - Jane, Kifi Abieyuwa; Omorogiuwa, T. B. E. (NIU Journal of Social Sciences, 2026)
Family planning plays a vital role in promoting maternal and child health, regulating population growth and enhancing the socio-economic stability of families. Despite the availability of various contraceptive methods, the attitudes of couples towards family planning remain influenced by multiple socio-cultural, religious and educational factors. The Objective of this study was to determine the attitudes of couples towards the use of family planning methods. A descriptive survey design was adopted, and data were collected using the structured questionnaire administered to a sample of married men and women. The findings suggest that efforts to improve family planning uptake must be context-sensitive, addressing not only individual knowledge gaps but also cultural norms, religious beliefs and socio-economic barriers that shape reproductive decisions. This study recommends that the Federal and State government should build reproductive health centers where family planning education would be given to couples on the choice of family planning for both educated and non-educated couples. Keywords: Family planning, Couple’s attitudes, Contraceptive methods, Reproductive health, Population control.